INFLUENCE OF RAINFALL ON DOWNY MILDEW INTENSITY, PRODUCTIVITY, AND SYMPTOMS OF Peronosclerospora spp. ATTACK IN MAIZE CROPS IN SIMALUNGUN REGENCY - Murni Radiah; Syamsafitri; Murni Sari Rahayu; Romi Fahri (RADJA PUBLIKA, 2025)
Maize is one of the world's food crops, and Simalungun Regency is one of the corn production centers in Indonesia. Corn production in Simalungun Regency has decreased due to various factors including downy mildew. Downy mildew disease is caused by Peronosclerospora spp. its development is increasingly rapid supported by a high humidity environment, while the purpose of the study was to examine the effect of rainfall on downy mildew disease intensity, productivity, production, and symptoms of corn plant attack in different locations.Research method: Observations of correlation and regression tests of rainfall on disease intensity, productivity, production, and harvest area of corn were analyzed using Minitab statistical application.The results showed that there is a relationship between rainfall and downy mildew intensity, production, productivity, and harvest area of corn plants. The intensity of downy mildew was highest in Tanah Jawa sub-district with an average disease intensity of 7.81%, this was due to the fact that no eradication was done on plants infected with Peronosclerospora spp. The symptoms of attack found at each observation location had the same symptoms.